Pembuatan Video Dokumenter Kegiatan Pengabdian Masyarakat - Yeni Rokhayati (Universitas Lancang Kuning, 2021)
Community service activities of the Batam State Polytechnic in 2018 are held together by all departments and taken place in Rempang Cate Village, Galang District, Batam City. A good documentation that can be seen more real is needed so that this activity can be better known by the outside community. One documentation that fulfills this expectation is a documentary video. This video production consists of 3 stages, namely pre-production, production, and post-production. The activity not only ends when the documentary video is finished, but continues with an evaluation to find out whether the video in presenting service activities is better when compared to ordinary documentation (by photo). Then, the video is published in the mass media, both print and electronic media. The results of the devotion to the making of this documentary video is the documentation of the community service of the Batam State Polytechnic in 2018 well and real, as well as the recognition of the Batam State Polytechnic and its social services in the wider community.